Professionalising English language teaching concepts and reflections for action in teacher education - Cirocki, Andrzej; Hallet, Wolfgang (Cambridge University Press, 2024)
The issue of professionalisation of English Language Teaching (ELT) remains underexplored in academic discourse. Written by experienced teacher educators, this book presents a timely guide to professional teacher development in ELT, showing how teacher educators and classroom practitioners can develop their practice. It scrutinises key topic areas for teacher education, detailing the specific competences that professional teachers need to demonstrate in the 21st century, including transforming English language classrooms, engaging in ongoing debates that examine theory, research and practice, responding to managerial and policy discourses on English language instruction, and playing a leading role in regulating the entire teaching profession. It highlights how meaningful, impactful, transformative, and sustainable language education requires high-quality teachers who are lifelong learners, classroom ethnographers, and educational leaders. It is essential reading for pre- and in-service teachers, teacher educators and professional development providers, educational researchers, as well as policy makers in the field of ELT.
Title from publisher's bibliographic system (viewed on 18 Oct 2024)
Keywords: English teachers / Training of; English language / Study and teaching